(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. The frequency of Helicobacter Pylori (HP) infection among patients with central serous chorioretinopathy (CSC) exceeds general national one. Purpose. To determine tomographic peculiarities of the central serous chorioretinopathy depending on the form of the disease and Helicobacter Pylori infection. Materials and methods. 93 patients with acute form, 15 — with primary chronic and 36 (44 eyes) with secondary chronic form of central serous chorioretinopathy were examined with the help of spectral OCT on the tomograph «SOCT Copernicus». Results. HP-positive patients with CSC are characterized by: frequency of combined neuro- and pigment retinal epithelium detachment (15.9 % eyes) was 2.1 times higher (p<0.0l), neuroepithelium detachment only (84.1 % eyes) -1.1 times lower (p[<0.05) than indices of HP-negative patients; height of the sack with sub-retinal fluid (219+82 nm) was 1.3 times lower, its width (3690+448 nm) — 1.2 times higher than indices of HP-negative patients (p[<0.05); central (175+17 nm) and general central foveal retinal thickness (395+40 nm) was 1.3 times decreased than indices of HP-negative patients (p[<0.05). Conclusions. Retinal tomographic peculiarities in patients with central serous chorioretinopathy depend on the form of the disease and Helicobacter Pylori infection.